A novel immersive calcium carbonate coating for conservation of limestone relics with a gypsum crust. (3rd August 2022) - Wang, Lu; He, Lu; Liu, Yan; Yang, Fuwei; Zhang, Kun; Chen, Xinnan; Gao, Xiang
Abstract : An immersive calcium carbonate coating has excellent permeability, compatibility and water stability for conserving surface weathered limestone relics. Abstract : A novel calcium carbonate coating was prepared to conserve limestone relics with a gypsum crust for the first time. In the preparation process, a solution of calcium hydroxy glycolate/urea was introduced into the gypsum crust and then transformed controllably into calcium carbonate when enough water was provided. The gypsum crust was thus immersively coated by the newly produced calcium carbonate and protected from the damage of water erosion. The conservation effect of the immersive calcium carbonate coating was investigated by scanning electron microscopy with energy-dispersive X-ray spectroscopy (SEM/EDX), Fourier transform infrared spectroscopy (FTIR), X-ray diffractometry (XRD), water erosion resistance, surface strength, surface hardness, color alteration, capillary water absorption and porosity tests. The results revealed that the immersive calcium carbonate coating had excellent permeability, compatibility and water stability, and would be a new solution for conserving surface weathered stone relics.